The Magnitude of Menu Costs: Direct Evidence from Large U.S. Supermarket Chains - Daniel Levy; Mark Bergen; Shantanu Dutta; Robert Venable (Quarterly Journal of Economics, 1997)
We use store-level data to document the exact process of changing prices and to directly measure menu costs at five multistore supermarket chains. We show that changing prices in these establishments is a complex process, requiring dozens of steps and a nontrivial amount of resources. The menu costs average 105,887/year per store, comprising 0.70 percent of revenues, 35.2 percent of net margins, and 0.52/price change. These menu costs may be forming a barrier to price changes. Specifically, (1) a supermarket chain facing higher menu costs (due to item pricing laws that require a separate price tag on each item) changes prices two and one-half times less frequently than the other four chains; (2) within this chain the prices of products exempt from the law are changed over three times more frequently than the products subject to the law.
Keywords: E12; E31; 330; Menu Cost; Posted Prices; Multiproduct Retailer; Price Rigidity; Sticky Prices; Rigid Prices; Cost of Price Adjustment; New Keynesian Economics; Time Dependent Pricing